(untitled) (GEOmedia, 2010)
Gi4DM - Geomatics for crisis management The recent disasters in Haiti, Chile, L’Aquila and Madeira underlined the importance of reliable geospatial datasets, used to better manage and organize rescue measures. The Gi4DM Conference, held in Turin last february, aimed at providing a scientific framework to all researchers and organizations that are envolved in the aftermath of these events.